Evaluation of inpatient services of tertiary comprehensive hospitals based on DRG payment - Yu, Qun-jun; Li, Ya-lin; Yin, Qin; Lu, Ye; Li, Lu-yan; Xu, Dan-ni; He, Mei; Ma, Sha; Yan, Wu (Frontiers in Public Health, 2024)
Objective: The relevant indicators from the Diagnosis Related Groups (DRG) payment system were used to evaluate inpatient services in 49 tertiary comprehensive hospitals. It will promote the optimization of medical services, and improve the efficiency and quality of inpatient care. Method: DRG data of 49 tertiary comprehensive hospitals was obtained from quality monitoring platform for provincial hospitals were used to the weight of each indicator by the analytic hierarchy process (AHP). The rank sum ratio method was used to calculate the WRSR value and the corresponding probit value of each hospital. The hospitals were divided into four grades based on the threshold value: excellent, good, fair and poor. Results: The 8 indicators of the 49 hospitals were input into the non-integer rank formula, and the rank scores of each indicator of individual hospital were obtained. The weight of each index and the rank of the corresponding index of the hospitals were substituted into the weighted rank sum ratio formula as well as the WRSR value of the hospitals were calculated. With Probit as the independent variable and WRSR as the dependent variable and the regression model was well-fitted. The ranking results of each hospital across various indicators were easily distinguishable. The classification calculation categorized the 49 hospitals into four groups: excellent (4), good (21), average (21), and poor (3). There were statistically significant differences in the average WRSR values of four categories of hospitals. Conclusion: There were notable variances in the levels of inpatient services among 49 tertiary comprehensive hospitals, and hospitals of the same category also showed different service levels. The evaluation of results could enhance resource allocation and refine medical processes to improve inpatient medical services.